THE DEVELOPMENT OF LEARNING SETS AND RESEARCH METHODOLOGY MODULE USING PROBLEM BASED LEARNING FOR ACCOUNTING EDUCATION STUDENTS - Thomas, Partono; Nurkhin, Ahmad (Journal of Accounting and Business Education, 2016)
Improving the learning process is very important for every lecturer by implement innovative learning methods or media. The purpose of this study is to develop a research methodology learning instruction and module based of problem based learning for accounting education students. This research applied research and development design in the research methodology course in Economics Education (Accounting) Department, Faculty Of Economics, Semarang State University. Data analysis was used to test the products through expert opinion (lecturer) and the feedback from students. The results show have been produced and tested two products, namely units lecture event and accounting education research methodology modules that implement problem-based learning methods. Some experts and students give positive feedback about the products.Keywords: problemÂ  based learning, modul, accounting education research methodology